Early enrichment in free-range laying hens: effects on ranging behaviour, welfare and response to stressors. (31st July 2017) - Campbell, D. L. M.; Hinch, G. N.; Downing, J. A.; Lee, C.
Abstract : Free-range laying hen systems are increasing within Australia. The pullets for these systems are typically reared indoors before being provided first range access around 21 to 26 weeks of age. Thus, the rearing and laying environments are disparate and hens may not adapt well to free-range housing. In this study, we reared 290 Hy-Line ® Brown day-old chicks divided into two rooms each with feed, water and litter. In the enriched room, multiple structural, manipulable, visual and auditory stimuli were also provided from 4 to 21 days, the non-enriched room had no additional objects or stimuli. Pullets were transferred to the laying facility at 12 weeks of age and divided into six pens (three enriched-reared, three non-enriched-reared) with identical indoor resources and outdoor range area. All birds were first provided range access at 21 weeks of age. Video observations of natural disturbance behaviours on the range at 22 to 23 and 33 to 34 weeks of age showed no differences in frequency of disturbance occurrences between treatment groups ( P =0.09) but a decrease in disturbance occurrences over time ( P <0.0001). Radio-frequency identification tracking of individually tagged birds from 21 to 37 weeks of age showed enriched birds on average, spent less time on the range each day ( P <0.04) but with a higher number of range visits than non-enriched birds from 21 to 24 weeks of age ( P =0.01). Enriched birds accessed the range on more days ( P =0.03) but over time, most birds in both treatment groups accessed the range daily. Basic external health scoring showed minimal differences between treatment groups with most birds in visibly good condition. At 38 weeks of age all birds were locked inside for 2 days and from 40 to 42 weeks of age the outdoor range was reduced to 20% of its original size to simulate stressful events. The eggs from non-enriched birds had higher corticosterone concentrations following lock-in and 2 weeks following range reduction compared with the concentrations within eggs from enriched birds ( P <0.0001). Correspondingly, the enriched hens showing a greater increase in the number of visits following range area reduction compared to non-enriched hens ( P =0.02). Only one rearing room per treatment was used but these preliminary data indicate 3 weeks of early enrichment had some long-term effects on hen ranging behaviour and enhanced hen's adaptability to environmental stressors.